Dynamics of sleep duration (2003-2018) and the risk of myocardial infarction in an open population aged 45-64 years in Russia/Siberia - V. V. Gafarov; E. A. Gromova; D. O. Panov; I. V. Gagulin; A. V. Gafarova (Российский кардиологический журнал, 2022)
Aim. To determine the dynamics and impact of sleep duration in 2003-2018 on the risk of myocardial infarction (MI) in an open population aged 45-64 years in Novosibirsk.Material and methods. The study included representative samples of the population aged 45-64 years, obtained as part of the screening IV in 2003-2005 (men, 576; mean age, 54,23±0,2 years; response rate, 61%; women, 1074; mean age, 54,27+0,2 years; response rate, 72%) and screening VI in 2015-2018 (men, n=275; mean age, 49±0,4 years; response, 72%; women, n=390; mean age, 45±0,4 years; response rate, 75%). Screenings were carried out according to the standard protocol of the WHO MONICA-psychosocial Program (MOPSY). The Jenkins Questionnaire was used to assess sleep duration and disturbances.Results. For the period from 2003-2005 to 2015-2018, we revealed decrease in the number of following people: with 7 hours of sleep at night from 44,9% to 31,9%; with 8 hours of sleep from 28,5% to 24,4%. In addition, the number of participants with ≤5 hours of sleep increased from 4,9% to 9,9%, while those with ≤6 hours — from 16,2% to 27,2%, as well as the number of people sleeping 9 hours a day (from 3,7% to 5,4%). In 2003-2005, among the population in the age group of 55- 64 years, 7-hour sleep was observed more often (45б1%); 6-hour sleep prevailed in the group of people aged 45-54 (18,9%). There were no significant differences between the duration of sleep and the age group according to screening VI in 2015- 2018. Among men, 6-hour sleep were observed more often (38.4%), and among women — 7 hours (37,3%). Those who sleep 7 hours a night were more likely to consider their sleep “good” (35,3%) in 2015-2018. In a population of 45-64 years old, over a 14-year period, the risk of MI was higher as follows: 1. in men with 5-6 hours of sleep than with 7-8 hours of sleep at night by 1,689 times (95% confidence interval (CI), 1,124-2,537 p<0,012); in men aged 45-54 years by 2,416 times (95% CI, 1,311-4,452; p<0,005), respectively; 2. in women with 5-6 hours of sleep by 1,591 times (95% CI, 1,058-2,392; p<0,026) compared with 7-8-hour duration of sleep. In the 45-54 year group, the risk of MI was higher among women with 9-10 hours of sleep a night by 4,44 times (95% CI, 2,726-20,309; p<0,0001) compared with women who had 7-8 hours of sleep at night.Conclusion. We revealed that over the period of 2003-2018, the duration of night sleep of 7-8 hours among the population aged 45-64 years (without cardiovascular diseases) decreased both among men and women. At the same time, the “good” quality of sleep was more often found in people with 7-hour sleep. It was determined that short sleep duration was associated with MI among men and women, and long sleep duration turned out to be a risk factor for MI for women in the group of 45-54 years.